Capture of perchlorate by a surface-modified bio-sorbent and its bio-regeneration properties: Adsorption, computations and biofouling. (October 2017) - Ren, Zhongfei; Xu, Xing; Gao, Baoyu; Li, Yanwei; Kong, Jian; Shang, Yanan; Song, Wen; Zhang, Qingzhu
Abstract: A magnetic amine-crosslinked reed (MACR) was synthesized by an insitu precipitation method and used for perchlorate uptake. The morphological properties of clean MACR, perchlorate-saturated MACR and bio-regenerated MACR samples were determined using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and zeta potential measurements. The adsorption capacities of perchlorate by clean and bio-regenerated MACRs were determined. The density functional theory (DFT) method was employed to evaluate the binding free energies between various anions and ammonium/hydroxy groups. The maximum adsorption (Qmax ) of perchlorate by MACR was calculated to be 195.5–232.8 mg/g at 30–50 °C. The theoretical computation of adsorption-free energies indicated that ammonium groups were dominant in the process of perchlorate adsorption; other anions, such as [H2 PO4 ] -, [NO3 ] - and [SO4 ] 2-, showed relatively higher binding free energies than [ClO4 ] -, which corresponded to the results of competitive adsorption. The spent MACR was then bio-regenerated in a sealed 250-ml conical flask with perchlorate-reducing bacteria (30 °C, 160 rpm) and reached 81.4% of recovery within 3 days. Some hydrophobic macromolecules of extracellular polymeric substances (EPS) might have attached to the surface of MACR, which was validated by the zeta potential, SEM and excitation emission matrix (EEM) fluorescence spectroscopy results. Graphical abstract: Highlights: We created a bifunctional bio-sorbent for ClO4 − capture. Laden perchlorate was directly reduced by the perchlorate reducing bacteria. A small biofouling was formed on bio-regenerated bio-sorbent due to the EPS. DFT analysis corresponded well to the competitive adsorption results.